Multifunctional Magnetic Ionic Liquid‐Carbon Nanohorn Complexes for Targeted Cancer Theranostics - Yun Qi; Eijiro Miyako (Small Science)
Establishing a rational and simplified design for nanoparticles that selectively target and eliminate cancer cells is a crucial aspect of cancer treatment. In this study, a new multifunctional nanocomplex is developed based on a photoexothermic carbon nanohorn comprising the magnetic and anticancer ionic liquids 1‐butyl‐3‐methylimidazolium tetrachloroferrate and fluorescent indocyanine green, synthesized through a convenient sonication process. The synthesized nanocomplexes exhibit unique therapeutic, photothermal, magnetic, and fluorescent properties, enabling chemotherapeutic, light‐, and magnetic‐field‐driven cancer theranostics. Furthermore, this nanocomplex demonstrates prolonged water‐dispersing stability (7 days), high photothermal conversion efficiency (63%), and remarkable stability under biologically permeable near‐infrared laser irradiation. Simple magnetic guidance significantly enhances the accumulation of nanocomplexes at tumor sites, facilitating targeted delivery. In vitro and in vivo studies have demonstrated potent anticancer efficacy, high selective cytotoxicity against cancer cells, and minimal impact on normal tissues. This study represents the first application of magnetic ionic liquids in cancer treatment and provides a valuable platform for advanced nanotheranostics.